Peranan Guru Agama Islam dalam Membelajarkan Siswa Menjadi Manusia yang Berakhlak Mulia - Umar, Jusnimar (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Al-Quran and al-ahadith  reveal a  lot about  the personality  of morality,  both in  the context of the vertical dimension of the relationship with Allah SWT. as well as horizontal relationships between  men and  their environment.  As a  matter of research,  feedback main theories in both these sources is needed. That is why morality is defined into the operational level that can be observed from the symptoms appear.This study focused on the role of religious teachers of Islam in teaching students to become human morality in SMPN 29 Bandar Lampung, includes objectives to be achieved, the  material  presented,  the  role  played  and  the  methods  used  Islamic  religious  teachers, motivated  students  to  become  a  man  of  morals  noble,  as  well  as  changes  in  behavior  and attitudes that result from learning morals in school, using a qualitative approach, in which the learning  process  and  results  are  described,  interpreted,  and  discussed  to find the essence of meaning.The series of answers to the problems above, a finding which is very beneficial for Islamic religious teachers to understand, appreciate and carry out its function as educators so that the learning process morals students they can do in a situation education comprehensively in order to produce a human figure that is more potent noble.